Corpora lutea affect in vitro maturation of bovine cumulus-oocyte complexes and embryonic development after fertilization with sex-sorted or conventional semen - Quezada Casasola, Andres (2020)
Influence of both the presence of a corpus luteum on the ovary and semen sex-sorting on development following in vitro fertilization is not yet conclusive. To determine the effect of these factors, 376 bovine oocytes were processed in vitro according to luteal presence on the ovary (CL+ and CL-) and type of semen used (sexed or conventional). Maturation rate was higher (P<0.01) in CL- (136/138; 98.6%), than in CL+ (217/238; 91.2%). Cleavage rate was lower (P<0.01) in CL+ with sexed semen (60/172; 34.9%) than in CL- with sexed semen (42/71; 59.1%) CL+ with conventional semen (47/66; 71.2%) and CL- with conventional semen (54/67; 85.1%). Compaction was similar (P=0.69) in CL- (49/99; 49.4%) and CL+ (50/107; 46.7%). Blastulation rate was higher (P<0.01) in CL- (26/99, 26.2%) than in CL+ group (13/107; 12.1%). Expansion rate was higher (P=0.01) in CL- (22/99; 22%) than in CL+ (11/107; 10.2%). Compaction rates were similar (P=0.78) in sex-sorted (50/102; 49.0%) or conventional semen (49/104; 47.1%) groups. Blastulation was also similar (P=0.91) with sex-sorted semen (19/102; 18.6%) and conventional semen (20/104; 19.2%). Rate of expanded blastocysts was similar (P=0.89) in sex-sorted (16/102; 15.6%) and conventional (17/104; 16.3%) semen groups. In conclusion, presence of CL can compromise maturation of the oocytes and their development, as a higher proportion of cleavage-stage embryos can be obtained with non-sexed semen with oocytes from ovaries without a CL.